2005
DOI: 10.1080/09286580590932743
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Color Blindness in Young Turkish Men

Abstract: We investigated a healthy population of men from different regions of Turkey for the presence of congenital red-green color blindness. Using Ishihara pseudoisochromatic plates, 941 healthy men from the Turkish army were tested for congenital red-green color blindness. The prevalence of red-green color blindness was 7.33 +/- 0.98% (5.10% protans and 2.23% deutans). These ratios were higher than other reported samples from Mediterranean Europe. Higher percentages of color blindness were found in regions with a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 13 publications
0
28
1
3
Order By: Relevance
“…Results from all these studies situated within the anticipated range for Caucasian males; about 8.0-10.0% of the Caucasian male population is affected [14]. CVD prevalence in neighboring countries are either lower or higher than this study results as (8.72) in Jordan [15] , In Iran, three studies are done in different cities in Qazvin, Zanjan , and Tehran, the prevalence of CVD were varied from 3.49 to 8.7 and 8.8 respectively [16][17][18],7.3% in Turkey [19], and 2.9-11% in Saudi Arabia [20][21]. In some European countries, in three different studies, the prevalence of CVD among male students in Germany were (7.8), (7.95) among males in Greek and (8.7) among males in Denmark [22][23][24].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Results from all these studies situated within the anticipated range for Caucasian males; about 8.0-10.0% of the Caucasian male population is affected [14]. CVD prevalence in neighboring countries are either lower or higher than this study results as (8.72) in Jordan [15] , In Iran, three studies are done in different cities in Qazvin, Zanjan , and Tehran, the prevalence of CVD were varied from 3.49 to 8.7 and 8.8 respectively [16][17][18],7.3% in Turkey [19], and 2.9-11% in Saudi Arabia [20][21]. In some European countries, in three different studies, the prevalence of CVD among male students in Germany were (7.8), (7.95) among males in Greek and (8.7) among males in Denmark [22][23][24].…”
Section: Discussionmentioning
confidence: 73%
“…In large study in India, researchers found that 7.95% deutans and 3.22% protans [26], In Jordan, 12 of cases of deutan and 7 cases of protans [15], In Nepal , 16 cases out of 19 cases of deutan types [27] , In study done in Philippine , (78.95%)of cases of CVD of deutan types [28]. In Erbil, cases of deutans are slightly more than cases of protans [8].while a Turkish study has reported about 5.10% protans and 2.23% deutans among male [29]. Because, the CVD is inherited the condition, its allocation is likely to be changeable among ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the previously published studies, the incidence of congenital colour vision defects recorded in different populations ranged from 2% to 8% of men (Malaspina et al 1986;Osuobeni 1996;Citirik et al 2005;Delpero et al 2005). Because the data collected by the Military Medical Commission showed only the general prevalence of colour vision defects, it was not possible to calculate the proportion of protans and deutans in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…A test score below 7 was considered color blind, and then classified as protananomalia or deuteranomalia. 1 Ishihara plates may have limitations, and the possibility exists that in some instances the failure to resolve such stimuli may indicate, not an absence of color resolution, but an inability to detect the critical features in the test. It can therefore be concluded that the Ishihara test is good for screening, but it does not discriminate complete and partial degrees of color blindness with accuracy.…”
mentioning
confidence: 99%